2021
DOI: 10.1108/itp-09-2019-0458
|View full text |Cite
|
Sign up to set email alerts
|

E-waste information security protection motivation: the role of optimism bias

Abstract: PurposeElectronic waste (e-waste) such as discarded computers and smartphones may contain large amounts of confidential data. Improper handling of remaining information in e-waste can, therefore, drive information security risk. This risk, however, is not always properly assessed and managed. The authors take the protection motivation theory (PMT) lens of analysis to understand intentions to protect one's discarded electronic assets.Design/methodology/approachBy applying structural equation modeling, the autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Janmaimool [31] studied food waste disposal behavior and found that threat appraisal composed of perceived severity and probability positively affected respondents' waste disposal behaviors. According to Chen et al's [36] electronic waste protection study, perceived threat as a threat appraisal positively affected information security protection intention. In terms of waste management behavior, according to Yusoff and Asmuni [33], threat appraisal positively affects waste disposal and reuse behaviors.…”
Section: Relationship Between Threat Appraisal and Ugly Food Purchase...mentioning
confidence: 99%
See 1 more Smart Citation
“…Janmaimool [31] studied food waste disposal behavior and found that threat appraisal composed of perceived severity and probability positively affected respondents' waste disposal behaviors. According to Chen et al's [36] electronic waste protection study, perceived threat as a threat appraisal positively affected information security protection intention. In terms of waste management behavior, according to Yusoff and Asmuni [33], threat appraisal positively affects waste disposal and reuse behaviors.…”
Section: Relationship Between Threat Appraisal and Ugly Food Purchase...mentioning
confidence: 99%
“…Shafiei and Maleksaeidi [38] studied university students' proenvironmental behaviors and found that students' self-efficacy positively affects proenvironmental behavior. Chen et al [36], in the context of an electronic waste study, reported that self-efficacy as a coping appraisal positively affected information security protection intention. Yusoff and Asmuni [33] indicated that coping appraisal positively affects waste disposal behavior.…”
Section: Relationship Between Coping Appraisal and Ugly Food Purchase...mentioning
confidence: 99%
“…Information security related to data in a discarded personal or professional digital device is probably important. However, there is also a lack of research focusing on information security from an e-waste perspective (Alghazo et al, 2018;Chen et al, 2022). Our study extends the breadth of such e-waste risks.…”
Section: Introductionmentioning
confidence: 86%
“…Thus, they feel less vulnerable to information security threats and more confident that they are protecting IS assets (Rhee et al. , 2005; Chen et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation